Solid electrolyte membrane and all-solid-state battery including the same
The integration of a fibrous binder with sulfide-based or halide-based solid electrolytes in a dry process creates a solid electrolyte membrane with enhanced ionic conductivity and mechanical strength, overcoming the limitations of existing all-solid-state battery technologies.
Patent Information
- Application Number
- JP2024557783
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-23
- Filing Date
- 2023-12-22
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-12-22
AI Technical Summary
Existing solid electrolytes for all-solid-state batteries face challenges in achieving both high ionic conductivity and mechanical strength, which are essential for ensuring safety and performance.
A solid electrolyte membrane is developed using a sulfide-based or halide-based solid electrolyte combined with a fibrous binder, where the binder is physically mixed and fiberized during a dry process, forming a cross-linked structure that enhances both ionic conductivity and tensile strength.
The resulting solid electrolyte membrane exhibits improved ionic conductivity (0.5 to 10 mS/cm) and tensile strength (45 to 1000 kPa), while being solvent-free, which addresses the limitations of previous technologies.
Smart Images

Figure 2025512868000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0182670 dated December 23, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a solid electrolyte membrane and an all-solid-state battery including the same. [Background technology]
[0003] From the viewpoints of battery capacity, safety, output, large size, ultra-compactness, and the like, various batteries capable of overcoming the limitations of lithium secondary batteries are currently being researched.
[0004] Representatively, research is being continuously conducted in academia and industry into metal-air batteries, which have a much larger theoretical capacity than lithium secondary batteries, all-solid-state batteries, which are safe and have no risk of explosion, supercapacitors in terms of output, NaS batteries or RFB (redox flow batteries) in terms of large size, and thin film batteries in terms of ultra-miniaturization.
[0005] An all-solid-state battery is a battery that replaces the liquid electrolyte used in conventional lithium secondary batteries with a solid electrolyte, and can significantly improve safety by not using flammable solvents in the battery and completely eliminating the risk of fire or explosion caused by the decomposition reaction of conventional electrolytes. In addition, since Li metal or Li alloy can be used as the anode material, it has the advantage of dramatically improving the energy density relative to the mass and volume of the battery.
[0006] However, although the use of the solid electrolyte in the all-solid-state battery can ensure safety, there is a possibility that the ionic conductivity may decrease, and if a liquid electrolyte is used together with the solid electrolyte to ensure the ionic conductivity of the solid electrolyte, there is a problem that the strength decreases.
[0007] Generally, in order to ensure the safety of an all-solid-state battery while preventing deterioration of the battery's performance and processability, both the ionic conductivity and strength of the solid electrolyte must be maintained at a certain level or higher.
[0008] However, among the solid electrolytes developed to date, there have been few technological developments that have achieved both ionic conductivity and strength.
[0009] As the demand for solid-state batteries increases, the demand for solid electrolytes contained in the solid-state batteries also increases proportionally. Therefore, there is a need to develop solid electrolytes having excellent ionic conductivity and strength. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Korean Patent Publication No. 2022-0095689 Summary of the Invention [Problem to be solved by the invention]
[0011] The present inventors have conducted extensive research to solve the above problems, and have found that a solid electrolyte membrane having improved ion conductivity and strength can be manufactured by a dry process in which a sulfide-based solid electrolyte and / or a halide-based solid electrolyte and a binder are physically mixed, and the fibrous binder is dispersed and entangled to form the structure.
[0012] It is therefore an object of the present invention to provide a solid electrolyte membrane with improved ionic conductivity and strength.
[0013] Another object of the present invention is to provide an all-solid-state battery including a solid electrolyte membrane with improved ionic conductivity and strength. [Means for solving the problem]
[0014] In order to achieve the above object, the present invention provides a solid electrolyte membrane comprising a solid electrolyte and a fiberized binder, the solid electrolyte comprising at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte.
[0015] The present invention also provides a solid electrolyte membrane, wherein the sulfide-based solid electrolyte is represented by the following chemical formula 1: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1, b1, c1, d1, and e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
[0016] The present invention also provides a solid electrolyte membrane, wherein the halide-based solid electrolyte is represented by the following chemical formula 2: [Chemical formula 2] Li 6-3a M a Br b Cl c In the above formula 2, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0017] The present invention also provides a solid electrolyte membrane, wherein the solid electrolyte is contained in an amount of 98 wt % or more based on the total weight of the solid electrolyte membrane.
[0018] The present invention also provides a solid electrolyte membrane, wherein the fibrous binder contains at least one selected from the group consisting of polytetrafluoroethylene (PTFE) and copolymers containing the same.
[0019] The present invention also provides a solid electrolyte membrane, wherein the fibrous binder is contained in an amount of 2 wt % or less based on the total weight of the solid electrolyte membrane.
[0020] The present invention also provides a solid electrolyte membrane, wherein the fibrous binder is contained in the solid electrolyte membrane in a dispersed state.
[0021] The present invention also provides a solid electrolyte membrane, in which the solid electrolyte and the fibrous binder are bonded to each other at an interface therebetween.
[0022] The present invention also provides a solid electrolyte membrane, wherein the solid electrolyte membrane has an ion conductivity of 0.5 to 10 mS / cm.
[0023] The present invention also provides the solid electrolyte membrane, wherein the solid electrolyte membrane has a tensile strength of 45 to 1000 kPa.
[0024] The present invention also provides a solid electrolyte membrane, wherein the solid electrolyte membrane is solvent-free.
[0025] The present invention also provides an all-solid-state battery comprising a positive electrode, a negative electrode, and the solid electrolyte membrane interposed between them. Effect of the Invention
[0026] The solid electrolyte membrane according to the present invention is composed of sulfide-based and / or halide-based solid electrolyte particles and a fibrous binder, and contains a small amount of the fibrous binder, so that the content of the solid electrolyte particles is relatively high, and the ion conductivity can be improved.
[0027] In addition, the solid electrolyte membrane includes a fibrous binder having an entangled structure in which the binder is fiberized during a dry process in which physical mixing is performed without using a solvent, and therefore can exhibit excellent tensile strength even when using only a small amount of the fibrous binder. [Brief description of the drawings]
[0028] [Figure 1] FIG. 2 is a schematic diagram showing an internal structure of a solid electrolyte membrane according to an embodiment of the present invention. [Diagram 2] 1 is a scanning electron microscope (SEM) photograph of a solid electrolyte membrane according to an embodiment of the present invention. [Diagram 3] 1 is a graph showing a correlation between the content of a fibrous binder contained in a solid electrolyte membrane according to an embodiment of the present invention and ionic conductivity and tensile strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The present invention will now be described in further detail to aid in the understanding of the present invention.
[0030] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that corresponds to the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0031] The term "crosslinked structure" as used herein refers to a structure formed by entanglement of fibrous binders dispersed in a solid electrolyte membrane, and may be a three-dimensional structure including a frame made of the fibrous binders and an internal space formed by the frame.
[0032] solid electrolyte membrane The present invention relates to a solid electrolyte membrane.
[0033] The solid electrolyte membrane according to the present invention includes a solid electrolyte and a fibrous binder, and the solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte.
[0034] FIG. 1 is a schematic diagram showing the internal structure of a solid electrolyte membrane according to an embodiment of the present invention.
[0035] Referring to FIG. 1, the solid electrolyte (10) may exist in a particulate state within the solid electrolyte membrane (1), and the fibrous binder (20) may be included in an entangled state. Specifically, the fibrous binder (20) may be dispersed and entangled to form a cross-linked structure. The cross-linked structure may include a frame made of the fibrous binder (20) and a void that is a space between the frame, and the solid electrolyte (10) particles may be located in the void. The solid electrolyte (10) may be a sulfide-based and / or halide-based solid electrolyte.
[0036] In one embodiment of the present invention, the interface between the solid electrolyte and the fibrous binder may be an adhesive.
[0037] Since the interface between the solid electrolyte and the fibrous binder is firmly bonded by pressure during the manufacturing process, even if a small amount of the fibrous binder is used, the strength of the solid electrolyte membrane can be prevented from decreasing. In addition, since bonding is also performed between the solid electrolytes, it can be further advantageous in improving the strength of the solid electrolyte membrane.
[0038] In one embodiment of the present invention, the ionic conductivity of the solid electrolyte membrane may be 0.5 to 10 mS / cm. Specifically, the ionic conductivity may be 0.5 mS / cm or more, 0.6 mS / cm or more, 0.8 mS / cm or more, 1 mS / cm or more, 1.5 mS / cm or more, or 2 mS / cm or more, and may be 3 mS / cm or less, 5 mS / cm or less, 8 mS / cm or less, or 10 mS / cm or less. The ionic conductivity may be measured at room temperature (25°C).
[0039] In one embodiment of the present invention, the tensile strength of the solid electrolyte membrane may be 45 to 1000 kPa, or may be 45 kPa or more, 50 kPa or more, 80 kPa or more, 100 kPa or more, 120 kPa or more, or 150 kPa or more, or may be 200 kPa or less, 300 kPa or less, 500 kPa or less, 700 kPa or less, 900 kPa or less, or 1000 kPa or less.
[0040] In one embodiment of the present invention, the solid electrolyte membrane may be solvent-free.
[0041] The solid electrolyte membrane does not contain any solvent because it is manufactured by a dry process in which the sulfide-based and / or halide-based solid electrolyte and a binder are physically mixed. In addition, the binder is fibrous due to the pressure during the dry process, and the fibrous binder is dispersed and entangled with each other to form a cross-linked structure. As a result, even if only a small amount of the binder is used, a solid electrolyte membrane with improved strength can be manufactured due to the structure formed by the fibrous binder.
[0042] In addition, since no separate solvent is used, it is possible to prevent a phenomenon in which the crystal structure of a sulfide-based and / or halide-based solid electrolyte is destroyed by the solvent, resulting in a decrease in ion conductivity.
[0043] Generally, a wet process performed for manufacturing a solid electrolyte membrane uses a solvent capable of dissolving a binder, which is located between solid electrolyte particles to provide adhesion.
[0044] Meanwhile, the dry process according to the present invention physically stretches the binder in the form of initial particles to form fibers without using a solvent. Therefore, the structure of the binder in the manufactured solid electrolyte membrane is different from the structure formed by the wet process, and the physical properties of the solid electrolyte membrane can be improved compared to the solid electrolyte membrane manufactured by the wet process. The binder in the form of initial particles is physically deformed by shear force when mixed with the electrolyte particles. In order to induce such physical deformation, a mortar, a ball mill, or a roll press can be introduced during mixing. In addition, as a binder that can effectively induce physical deformation, a binder that is physically very weak and relatively easy to be fiberized, such as PTFE, can be used.
[0045] In an embodiment of the present invention, the solid electrolyte may include a sulfide-based solid electrolyte and / or a halide-based solid electrolyte.
[0046] The solid electrolyte may be contained in an amount of 98 wt% or more based on the total weight of the solid electrolyte membrane. Specifically, the content of the solid electrolyte may be 98 wt% or more, 98.5 wt% or more, or 99 wt% or more. If the content of the solid electrolyte is less than 98 wt%, the ion conductivity of the solid electrolyte membrane may be reduced. The upper limit of the content of the solid electrolyte is not particularly limited, but may be, for example, 99.8 wt% or less. If the content exceeds 99.8 wt%, the binder content is relatively reduced, and the tensile strength may be somewhat reduced.
[0047] The solid electrolyte may be particulate, and its particle size (D50) may be 10 nm to 10 μm, specifically, 10 nm or more, 100 nm or more, 300 nm or more, 500 nm or more, 800 nm or more, 1 μm or more, 2 μm or more, or 3 μm or more, and may be 5 μm or less, 7 μm or less, 9 μm or less, or 10 μm or less. If the particle size (D50) of the solid electrolyte is less than 10 nm, the tensile strength may decrease, and if it exceeds 10 μm, the surface of the solid electrolyte membrane may not be uniform, and the resistance with the electrode may increase.
[0048] In one embodiment of the present invention, the sulfide-based solid electrolyte may be represented by the following Chemical Formula 1: [Chemical formula 1]
[0049] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1, b1, c1, d1, and e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
[0050] For example, the sulfide-based solid electrolyte may include at least one selected from the group consisting of LiPSX (X=Cl, Br, or I)-based solid electrolytes, LiGePS-based solid electrolytes, and LiPS-based solid electrolytes. However, the sulfide-based solid electrolyte is not limited thereto, and a wide range of sulfide-based solid electrolytes commonly used in the art may be used. For example, the LiPSX (X=Cl, Br, or I) may be Li6PS5Cl.
[0051] In one embodiment of the present invention, the halide-based solid electrolyte may be represented by the following Chemical Formula 2: [Chemical formula 2] Li 6-3a Ma Br b Cl c In Chemical Formula 2, M is a metal other than Li, 0 < a < 2, 0 ≤ b ≤ 6, 0 ≤ c ≤ 6, and b + c = 6. Further, M may be Y, In, or Zr.
[0052] For example, the halide-based solid electrolyte may include one or more selected from the group consisting of Li3YBr6, Li3YCl6, and Li3YBr2Cl4.
[0053] In one embodiment of the present invention, the binder is fibrillated during a dry process in which it is physically mixed and pressed with the sulfide-based and / or halide-based solid electrolyte, and the fibrous binder can form a crosslinked structure in a dispersed and intertwined state with each other.
[0054] The binder may be one or more selected from the group consisting of polytetrafluoroethylene (PTFE) and copolymers containing the same, but is not limited thereto. A binder having low ductility strength and being easily stretched during the dry process and capable of being fibrillated into a fibrous binder can be widely used.
[0055] Further, the binder may be included at 2% by weight or less based on the total weight of the solid electrolyte membrane. Specifically, the content of the binder may be 2% by weight or less, 1.5% by weight or less, or 1% by weight or less. When the content of the binder exceeds 2% by weight, the ionic conductivity of the solid electrolyte membrane may decrease. Also, the lower limit of the binder is not particularly limited, but for example, it may be 0.2% by weight or more, and when it is less than 0.2% by weight, the tensile strength may decrease somewhat.
[0056] Method for manufacturing a solid electrolyte membrane The present invention also relates to a method for manufacturing the solid electrolyte membrane.
[0057] The method for producing a solid electrolyte membrane according to the present invention includes a step of mixing a solid electrolyte with a binder. The solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte. The solid electrolyte may be in a particulate form.
[0058] At this time, the types, contents and characteristics of the solid electrolyte and binder are as described above.
[0059] In addition, the solid electrolyte and the binder are physically mixed without any separate chemical reaction, so the mixing can be called physical mixing. The mixing can be performed using a mortar, ball mixing, or roll pressing. In order to facilitate the fiberization of the binder, the mixing time, the number of repetitions, or the addition of a heating process can be appropriately set.
[0060] All solid state battery The present invention also relates to an all-solid-state battery comprising the solid electrolyte membrane.
[0061] The all-solid-state battery according to the present invention includes the solid electrolyte membrane; a positive electrode formed on one side of the solid electrolyte membrane; and a negative electrode formed on the other side of the solid electrolyte membrane.
[0062] In an embodiment of the present invention, the positive electrode may include a positive electrode active material, a conductive material, and a binder.
[0063] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0064] The positive electrode active material layer includes a positive electrode active material, a conductive material, and a binder.
[0065] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), Li[Ni x Co y Mn z M v ]O2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In; 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti; M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N); 1+y Mn 2-y Lithium manganese oxides such as LiMnO4 (where y is 0 to 0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-y Ni-site type lithium nickel oxide represented by MyO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M y Examples of the lithium manganese composite oxides include, but are not limited to, lithium manganese composite oxides represented by the formula LiMn2O2 (wherein M is Co, Ni, Fe, Cr, Zn, or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu, or Zn); LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.
[0066] The positive electrode active material may be included in an amount of 60 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material may be 60 wt %, 65 wt % or more, or 68 wt % or more, and may be 72 wt % or less, 75 wt % or less, or 80 wt % or less. If the content of the positive electrode active material is less than 60 wt %, the battery performance may be reduced, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0067] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery, does not induce chemical changes in the battery, and has excellent electrical conductivity. Representative examples include graphite or conductive carbon, and include, for example, graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon-based materials having a graphene or graphite crystal structure; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives; which may be used alone or in combination of two or more kinds, but are not necessarily limited thereto. Preferably, the conductive material may include vapor-grown carbon fiber (VGCF).
[0068] The conductive material may be contained in an amount of 1 wt% to 5 wt% based on the total weight of the positive electrode active material layer. Specifically, the content of the conductive material may be 1 wt% or more, 1.5 wt% or more, or 2 wt% or more, and 4 wt% or less, 4.5 wt% or less, or 5 wt% or less. If the content of the conductive material is less than 1 wt%, the effect of improving electrical conductivity may be difficult to expect, or the electrochemical properties of the battery may be deteriorated, and if the content is more than 5 wt%, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of including the conductive material in the positive electrode is not significantly limited, and a conventional method known in the art, such as mixing with the positive electrode active material or coating, may be used.
[0069] The binder is a component that aids in bonding the positive electrode active material to the conductive material and the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile ...rolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyepi The binder may include one or more selected from the group consisting of cellulose acetate, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include polytetrafluoroethylene (PTFE).
[0070] In addition, the binder may be included in an amount of 0.5 wt% to 4 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content may be 0.5 wt% or more, 1 wt% or more, or 1.5 wt% or more, and 3 wt% or less, 3.5 wt% or less, or 4 wt% or less. If the binder content is less than 0.5 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 4 wt%, the adhesive strength is improved, but the content of the positive electrode active material may decrease accordingly, and the battery capacity may decrease.
[0071] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0072] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0073] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and may have various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, a nonwoven fabric, etc.
[0074] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition onto the current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropyl alcohol, etc. may be used.
[0075] In the present invention, the negative electrode included in the all-solid-state battery may include a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.
[0076] The negative electrode active material is lithium (Li +The lithium-containing compound may include a material capable of reversibly intercalating or deintercalating lithium ions, a material capable of reversibly forming a lithium-containing compound by reacting with lithium ions, lithium metal, or a lithium alloy.
[0077] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium-containing metal oxide (Li) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of indium (In), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0078] Preferably, the negative electrode active material may be lithium metal or a lithium-indium alloy (Li-In), specifically, it may be in the form of a lithium metal or lithium thin film or a lithium-indium alloy thin film or powder.
[0079] The negative electrode active material may be included in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more, and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0080] The binder is the same as that described above in the positive electrode active material layer.
[0081] The conductive material is the same as that described above in the positive electrode active material layer.
[0082] The negative electrode current collector is not particularly limited as long as it does not induce a chemical change in the battery and has conductivity, and for example, the negative electrode current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector may be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., having fine irregularities formed on the surface.
[0083] The method for manufacturing the negative electrode is not particularly limited, and the negative electrode may be manufactured by forming a negative electrode active material layer on a negative electrode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the negative electrode of the present invention also includes a case where a thin metallic lithium film is formed on a metal plate by initial charging after assembling a battery without a thin lithium film on the negative electrode current collector.
[0084] Manufacturing method for all-solid-state batteries The present invention also relates to a method for producing an all-solid-state battery.
[0085] The method for manufacturing an all-solid-state battery according to the present invention includes the steps of (P1) placing a mixture for forming a positive electrode active material layer on one side of a solid electrolyte membrane and applying pressure to form a positive electrode on one side of the solid electrolyte membrane; and (P2) placing a negative electrode on the other side of the solid electrolyte membrane and applying pressure.
[0086] In the step (P1), a mixture for forming a positive electrode active material layer may be placed on one side of the solid electrolyte membrane, and then pressurized at high temperature to form a positive electrode on one side of the solid electrolyte membrane.
[0087] The mixture for forming the positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder. The specific types and weights of these are as described above. In addition, after the positive electrode active material layer is formed, a current collector may be attached to the positive electrode to manufacture the positive electrode.
[0088] The pressurizing step is for bonding the solid electrolyte membrane and the positive electrode while reducing the interfacial resistance, and may be performed at a pressure of 300 MPa to 500 MPa. The pressure of the high-temperature pressurizing step may be 300 MPa or more, 350 MPa or more, or 400 MPa or more, and may be 450 MPa or less, 470 MPa or less, or 500 MPa or less. If the temperature and / or pressure of the high-temperature pressurizing step is below the above range, the solid electrolyte membrane and the positive electrode may not be integrated, and if it exceeds the above range, the solid electrolyte membrane or the positive electrode may be deformed or damaged.
[0089] In the step (P2), a negative electrode is placed on the other side of the solid electrolyte membrane and pressurized to manufacture an all-solid-state battery. The negative electrode has been described above.
[0090] The pressure during the pressurization may be 40 MPa to 80 MPa, specifically, the pressure during the pressurization may be 40 MPa or more, 45 MPa or more, or 50 MPa or more, and may be 70 MPa or less, 75 MPa or less, or 80 MPa or less. If the pressure during the pressurization is less than 40 MPa, the interfacial resistance between the negative electrode and the solid electrolyte membrane may increase, and if it exceeds 80 MPa, the solid electrolyte or the negative electrode may be deformed or damaged.
[0091] The all-solid-state battery manufactured in this manner includes a thin solid electrolyte membrane, and therefore the manufacturing cost can be reduced and the ion conductance and energy density can be improved.
[0092] In addition, since the solid electrolyte and the positive electrode are integrated by a high-temperature pressurizing process, the interface stability can be improved.
[0093] Battery Module The present invention also relates to a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0094] Specific examples of the device include, but are not limited to, power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.
[0095] In a preferred embodiment of the present invention, the solid electrolyte membrane comprises a solid electrolyte; and a fibrous binder, The solid electrolyte includes at least one of a sulfide-based solid electrolyte and a halide-based solid electrolyte, The sulfide-based solid electrolyte is represented by the following chemical formula 1: The halide-based solid electrolyte may be represented by the following Chemical Formula 2: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5. [Chemical formula 2] Li 6-3a M a Br bCl c In the above formula 2, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0096] In a preferred embodiment of the present invention, the sulfide-based solid electrolyte may include one or more selected from the group consisting of a LiPSX (X=Cl, Br, or I)-based solid electrolyte, a LiGePS-based solid electrolyte, and a LiPS-based solid electrolyte.
[0097] In a preferred embodiment of the present invention, the LiPSX (X=Cl, Br or I) based solid electrolyte may be Li6PS5Cl.
[0098] In a preferred embodiment of the present invention, the halide-based solid electrolyte may contain one or more selected from the group consisting of Li3YBr6, Li3YCl6, and Li3YBr2Cl4.
[0099] In a preferred embodiment of the present invention, the solid electrolyte may be contained in an amount of 98% by weight or more based on the total weight of the solid electrolyte membrane.
[0100] In a preferred embodiment of the present invention, the solid electrolyte may be in a particulate form, and the particle size (D50) may be from 10 nm to 10 μm.
[0101] In a preferred embodiment of the present invention, the fibrous binder may contain one or more materials selected from the group consisting of polytetrafluoroethylene (PTFE) and copolymers containing the same.
[0102] In a preferred embodiment of the present invention, the fibrous binder may be contained in an amount of 2% by weight or less based on the total weight of the solid electrolyte membrane.
[0103] In a preferred embodiment of the present invention, the fibrous binder may be contained in the solid electrolyte membrane in a dispersed state.
[0104] In a preferred embodiment of the present invention, the fibrous binder may be one that forms a cross-linked structure in which the fibrous binders are entangled with one another.
[0105] In a preferred embodiment of the present invention, the interface between the solid electrolyte and the fibrous binder may be one in which the solid electrolyte is bonded to the fibrous binder.
[0106] In a preferred embodiment of the present invention, the solid electrolyte membrane may have an ionic conductivity of 0.5 to 10 mS / cm.
[0107] In a preferred embodiment of the present invention, the solid electrolyte membrane may have a tensile strength of 45 to 1000 kPa.
[0108] In a preferred embodiment of the present invention, the solid electrolyte membrane may be solvent-free.
[0109] In a preferred embodiment of the present invention, the solid electrolyte may include a sulfide-based solid electrolyte represented by Chemical Formula 1.
[0110] In a preferred embodiment of the present invention, the solid electrolyte may include a halide-based solid electrolyte represented by Chemical Formula 2.
[0111] In a preferred embodiment of the present invention, the method for producing the solid electrolyte membrane includes a step of mixing a solid electrolyte and a binder, applying pressure to the solid electrolyte and forming the binder into a fiber in a solvent-free state, The solid electrolyte includes at least one of a sulfide-based solid electrolyte and a halide-based solid electrolyte, The sulfide-based solid electrolyte is represented by the following chemical formula 1: The halide-based solid electrolyte may be represented by the following Chemical Formula 2: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5. [Chemical formula 2] Li 6-3a M a Br b Cl c In the above formula 2, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0112] In a preferred embodiment of the present invention, the fibrous binder may be one that forms a cross-linked structure in which the fibrous binders are entangled with one another.
[0113] In a preferred embodiment of the present invention, the solid electrolyte membrane may have an ionic conductivity of 0.5 to 10 mS / cm.
[0114] In a preferred embodiment of the present invention, the all-solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane interposed between the positive electrode and the negative electrode, The solid electrolyte membrane includes a solid electrolyte; and a fibrous binder. The solid electrolyte includes at least one of a sulfide-based solid electrolyte and a halide-based solid electrolyte, The sulfide-based solid electrolyte is represented by the following chemical formula 1: The halide-based solid electrolyte may be represented by the following Chemical Formula 2: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1 to e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5. [Chemical formula 2] Li 6-3a M a Br b Cl c In the above formula 2, M is a metal other than Li, and a is 0. <a<2であり、bは0≦b≦6であり、cは0≦c≦6であり、b+c=6である。
[0115] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications also fall within the scope of the appended claims.
[0116] In the following Examples and Comparative Examples, solid electrolyte membranes were produced according to the compositions and steps shown in Table 1 below.
[0117] [Table 1]
[0118] Example 1 The sulfide-based solid electrolyte Li6PS5Cl powder was mixed with the binder PTFE particles (polytetrafluoroethylene, Chemours) in a mortar, and the resulting mixture was calendared five times in a roll press to produce a 300 μm thick solid electrolyte membrane.
[0119] Example 2 The same procedure as in Example 1 was repeated, except that the content of the binder was 0.5 wt % based on the total weight of the solid electrolyte membrane.
[0120] Example 3 The same procedure as in Example 1 was repeated, except that the content of the binder was 2 wt % based on the total weight of the solid electrolyte membrane.
[0121] Example 4 The same procedure as in Example 1 was repeated, except that the content of the binder was 5 wt % based on the total weight of the solid electrolyte membrane.
[0122] Comparative Example 1 The same procedure as in Example 1 was carried out, except that the solid electrolyte membrane was produced by a wet process using a solvent.
[0123] For the wet process, a xylen solvent that is stable for sulfide-based solid electrolytes was used.
[0124] A solution of PTFE particles, which is a binder, was prepared by dissolving it in a xylene solvent at a concentration of 5 wt%, and the mixture was mixed with Li6PS5Cl powder, which is a sulfide-based solid electrolyte, and the mixture was coated on a PET (polyethylene terephthalate) release film with a doctor blade, and then vacuum dried for 12 hours at 100° C. The binder was adjusted to be 0.2 wt % of the total weight of the solid electrolyte membrane.
[0125] Comparative Example 2 A solid electrolyte membrane was produced in the same manner as in the wet process of Comparative Example 1, except that NBR (nitrile-butadiene rubber) was used as the binder instead of PTFE. NBR is a binder commonly used in wet processes and is easily dissolved in a solvent.
[0126] Comparative Example 3 A solid electrolyte membrane was produced in the same manner as in Comparative Example 2, except that the content of NBR as a binder was 5% by weight.
[0127] Experimental Example 1: Internal structure of solid electrolyte membrane An experiment was carried out to confirm the internal structure of the solid electrolyte membrane produced in Example 1.
[0128] FIG. 2 is a scanning electron microscope (SEM, FEI Apreo SEM) photograph of the solid electrolyte membrane produced in Example 1.
[0129] 2, an entangled cross-linked structure was observed inside the solid electrolyte membrane of Example 1. It can be seen that the structure was formed by the entanglement of the fibrous binder after the binder was fiberized during the dry process.
[0130] Experimental Example 2: Measurement of ionic conductivity and tensile strength of solid electrolyte membrane In order to confirm the correlation between the binder content and the ionic conductivity of the solid electrolyte, the ionic conductivity of the solid electrolyte membrane was measured.
[0131] (1) Measurement of ionic conductivity To measure the ionic conductivity of the solid electrolyte membrane, the solid electrolyte membrane was placed in a polyether ether ketone (PEEK) holder with a diameter of 10 mm, and a titanium rod was used as a blocking electrode to measure the ionic conductivity.
[0132] Using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument), the resistance was measured at 25° C. under conditions of an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and then the ionic conductivity of the solid electrolyte membrane was calculated using the following Equation 1.
[0133] [Formula 1]
number
[0134] In the above formula 1, σ i is the ionic conductivity (mS / cm) of the solid electrolyte membrane, R is the resistance (Ω) of the solid electrolyte membrane measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the solid electrolyte membrane, and A is the area (cm 2 )
[0135] (2) Measurement of tensile strength The solid electrolyte membrane was cut into a size of 10mm x 50mm. In order to minimize damage to the solid electrolyte membrane caused by the clamp during measurement, tape was attached to both ends of the sample, and the tensile strength was measured using UTM (Universal Testing Machine, MARK-10, M5-05) equipment.
[0136] (3) Correlation between binder content and ionic conductivity and tensile strength X, which indicates the correlation between the binder content and the ionic conductivity and tensile strength, is calculated by the following formula 2. When X is 170 to 1000, it is determined that the solid electrolyte membrane has excellent ionic conductivity and tensile strength: [Formula 2] X=(b*c) / a In the formula 2, a is the content of the binder contained in the solid electrolyte membrane, b is the ionic conductivity of the solid electrolyte membrane, and c is the tensile strength of the solid electrolyte membrane.
[0137] [Table 2]
[0138] FIG. 3 is a graph showing the correlation between the content of the binder contained in the solid electrolyte membrane according to one embodiment of the present invention and the ionic conductivity and tensile strength.
[0139] Referring to FIG. 3, it was confirmed that the binder content and the ionic conductivity were inversely proportional, and the binder content and the tensile strength were proportional.
[0140] In Example 1 and Comparative Example 1, the solid electrolyte membrane was produced by a dry process and a wet process, respectively. In the wet process of Comparative Example 1, PTFE was not fiberized, so a cross-linked structure could not be formed, and the strength was therefore weak, so that the membrane could not be produced.
[0141] In addition, in Comparative Example 2, a solid electrolyte membrane was manufactured using a wet process such as a conventional slurry coating process, but since the content of NBR, a binder commonly used in wet processes, was low, it did not have the strength to function as a solid electrolyte membrane and could not be manufactured in the form of a membrane. In Comparative Example 3, although the content of NBR, a binder, was high, it was confirmed that the strength and ionic conductivity were lower than those of a solid electrolyte membrane manufactured using a wet process compared to those manufactured using a dry process.
[0142] Although the present invention has been described above using limited examples and drawings, the present invention is not limited thereto, and it is of course possible for a person having ordinary knowledge in the technical field to which the present invention pertains to make various modifications and variations within the technical spirit of the present invention and the equivalent scope of the claims described below. [Explanation of symbols]
[0143] 1: Solid electrolyte membrane 10: (Sulfide and / or halide) solid electrolyte 20: Fibrous binder
Claims
1. A solid electrolyte membrane comprising a solid electrolyte and a fiberized binder, The solid electrolyte membrane, wherein the solid electrolyte includes at least one selected from the group consisting of a sulfide-based solid electrolyte and a halide-based solid electrolyte.
2. The sulfide-based solid electrolyte is represented by the following chemical formula 1: [Chemical formula 1] L a1 M b1 P c1 S d1 A e1 In the above Chemical Formula 1, L is an element selected from Li, Na, and K, M is an element selected from B, Zn, Sn, Si, Cu, Ga, Sb, Al, and Ge, A is I, Br, Cl, or F, a1, b1, c1, d1, and e1 are composition ratios of each element, and a1:b1:c1:d1:e1 is 1-12:0-1:1:2-12:0-5.
3. The halide-based solid electrolyte is represented by the following chemical formula 2: [Chemical formula 2] Li 6-3a M a Br b Cl c In Formula 2, M is a metal other than Li, a is 0<a<2, b is 0≦b≦6, c is 0≦c≦6, and b+c=6.
4. 2. The solid electrolyte membrane according to claim 1, wherein the solid electrolyte is contained in an amount of 98% by weight or more based on the total weight of the solid electrolyte membrane.
5. 2. The solid electrolyte membrane according to claim 1, wherein the fibrous binder comprises at least one selected from the group consisting of polytetrafluoroethylene (PTFE) and copolymers containing the same.
6. 2. The solid electrolyte membrane according to claim 1, wherein the fibrous binder is contained in an amount of 2 wt % or less based on the total weight of the solid electrolyte membrane.
7. 2. The solid electrolyte membrane according to claim 1, wherein the fibrous binder is contained in the solid electrolyte membrane in a dispersed state.
8. The solid electrolyte membrane according to claim 1 , wherein the interface between the solid electrolyte and the fibrous binder is adhesive.
9. 2. The solid electrolyte membrane according to claim 1, wherein the ionic conductivity of the solid electrolyte membrane is 0.5 to 10 mS / cm.
10. 2. The solid electrolyte membrane according to claim 1, wherein the solid electrolyte membrane has a tensile strength of 45 to 1000 kPa.
11. 10. The solid electrolyte membrane of claim 1, wherein the solid electrolyte membrane is solvent-free.
12. An all-solid-state battery comprising a positive electrode, a negative electrode, and the solid electrolyte membrane according to any one of claims 1 to 11 interposed between them.
Citation Information
Patent Citations
Fabric reinforced sulfide solid electrolyte as well as dry preparation method and application thereof
CN114400370A
Gel-like polymer electrolyte and electrochemical device equipped therewith
JP2010503175A
Method for manufacturing a solid electrolyte membrane or anode, and solid electrolyte membrane or anode
JP2022514039A
Ion conductor material and battery
WO2020261758A1
All-solid-state secondary cell mixture, all-solid-state secondary cell mixture sheet, method for manufacturing same, and all-solid-state secondary cell
WO2022050252A1